Coupling of Architectural and Stereomicrostructural Engineering Toward Polyhydroxyalkanoate Mono-Materials - Gace, Maelle Therese, author; Chen, Eugene Y.-X. E., advisor; Prieto, Amy L. A., committee member; Herrera-Alonso, Margarita M., committee member; Miyake, Garret M. M., committee member (Colorado State University. Libraries, 2026)
The growing environmental concern surrounding plastic waste stems from the chemical complexity of conventional multi-material products, as these products are typically composed of distinct polymers designed to meet the diverse performance demands of modern applications. Although this compositional complexity enables enhanced functionality and performance, it also poses significant challenges for end-of-life (EoL) management, as the different polymer components are often immiscible, incompatible, and difficult to separate, thereby reducing the efficiency and effectiveness of mechanical, chemical, and biodegradation/composting recycling processes. In response, the concept of mono-material product design has emerged as a promising strategy toward more sustainable plastic product design, wherein a single polymer is engineered to access a broad spectrum of material properties or, in the case of multi-component systems, maintain compatibility within a common EoL pathway. Building on this concept, this dissertation focuses on the molecular engineering of biodegradable polyhydroxyalkanoates (PHAs) through stereomicrostructural, architectural, and topological design.This work demonstrates that stereochemical control and architectural design together enable access to a broad, tunable property space within a single polymer platform. In particular, reducing stereoregularity and introducing star architectures in poly(3-hydroxybutyrate) (P3HB), a biopolymer that is inherently brittle (~5% elongation at break) in its stereoregular form, produces synergistic effects across thermal behavior, crystallization, mechanical performance, rheology, and barrier properties. These changes in molecular design result in modulation of material behavior without altering polymer composition. This approach can be further extended to other diolide systems, reinforcing architectural engineering as a generalizable strategy across PHA systems.Moreover, a stereochemical continuum approach was developed, in which controlled polymerization of diastereomeric monomer mixtures of the eight-membered dimethyl diolide (8DLMe) yields P3HB materials spanning rigid thermoplastics, elastomers, and pressure-sensitive adhesives (PSA) within a single polymer system. This strategy enables the fabrication of an all-P3HB PSA tape prototype, demonstrating the feasibility of mono-material product design from a single polymer. Finally, chemocatalytic synthesis is used to access stereoregular poly(3-hydroxyhexanoate) (P3HHx) homopolymers and P3HB-based statistical and triblock copolymers. These materials exhibit wide-ranging thermal and mechanical properties, including high modulus, high ductility, and extended thermal operating windows, further highlighting the versatility of stereochemistry and monomer feed ratio in tuning material properties. Overall, this dissertation establishes a unified framework for expanding the design space of PHAs through stereomicrostructural and architectural engineering. This work provides a foundation for designing sustainable mono-material plastics capable of achieving diverse material properties and performance within a single polymer system, thereby enabling more sustainable end-of-life management and reducing environmental impact.